Predictors of Birth Preparedness and Complication Readiness Practices Among Pregnant Women in Ethiopia, a Systematic Review and Meta-Analysis - Alamrew, Abebaw; Ayele, Mulat; Shitie Lake, Eyob; Mulugeta, Chalie; Kumie, Getinet; Birara Zemariam, Alemu (International Journal of Public Health, 2024)
We did this review to identify factors associated with Birth preparedness and complication readiness (BPCR) practice among pregnant women in Ethiopia. BPCR is a comprehensive approach that helps resolve delays in seeking care for obstetric problems. Methods: PRISMA was followed and different databases were used to find studies. Adjusted Odds Ratio (AOR) with 95% Confidence Interval was used to identify factors. I 2 statistics, funnel plot, and Egger test were used to assess the studies' heterogeneity and publication bias.